The impact of implementing a scientific approach on the science learning achievements of 4th-grade students within the learning environment - Cahyono, Budi Tri; Ridhani, Jovita; Qodr, Taufiq Subhanul; Khan, Nauroz; Ali, Wazir (Journal of Environment and Sustainability Education, 2025)
This study investigates the influence of a scientific approach on the academic performance of 4th students in science.  The scientific approach focuses on key processes such as observation, formulating questions, making connections, conducting experiments, analyzing data, drawing conclusions, and presenting findings, distinguishing it from traditional science education methods.  Employing a quantitative research design with a quasi-experimental non-equivalent control group, the study targeted all Gugus I Gajah Mada Laweyan Surakarta 4th students.  A sample of 120 students from eight elementary schools was selected, with participants divided into experimental and control groups, each comprising 60 students.  Data collection involved both observational methods and essay assessments featuring 30 questions.  The findings revealed a notable disparity in science learning outcomes between students instructed using the scientific approach and those who received conventional instruction.  Specifically, students in the experimental group demonstrated significantly superior learning outcomes compared to their counterparts in the control group. The results of the study showed that the assessment of learning outcomes using observation sheets had a significant effect on teacher involvement during the learning process.  The results of the Lillefors Statistical test show the difference between scientific and conventional classes, with the former showing a higher value of 0.95 compared to 0.87.  This indicates that the use of digital learning media effectively attracts the interest of students and teachers.